xsl-list
[Top] [All Lists]

## Re: [xsl] Two versions of sum over node list by recursion--why and how does second one work?

2006-09-05 10:42:21
```Both are a correct way of expressing the sum.

Dr. Kay's solution is a special case of using the foldr() function,
the Haskell definition of which is below:

foldr f z [ ] = z
foldr f z (x:xs) = f x (foldr f z xs)

G.Ken Hollman's solution is a special case of using the foldl()
function, the Haskell definition of which is below:

foldl f z [ ] = z
foldl f z (x:xs) = foldl f (f z x) xs

Both foldr() and foldl() are fundamental functions, implemented in FXSL.

To conclude this, one can also express the solution to this problem as
a special case of using the FXSL f:product() function (which is itself
trivially defined using f:foldl() or f:foldr()):

sum(  f:map( f:compose(f:product(), f:childElements() ), *)  )

--
Cheers,
Dimitre Novatchev
---------------------------------------
Truly great madness cannot be achieved without significant intelligence.
---------------------------------------
To invent, you need a good imagination and a pile of junk

On 9/5/06, hanged(_dot_)man(_at_)lycos(_dot_)com
<hanged(_dot_)man(_at_)lycos(_dot_)com> wrote:
```
```Here are two examples of summing a node list by recursion: the first sends
the result of the addition back to itself by a parameter: the second does
not. The first was posted by G. Ken Holman--the second is from Michael Kay
s _XSLT Programmer's Reference_.

I know that Mr. Kay's code works...I just can't figure out _why_.

FIRST EXAMPLE:

<xsl:template match="/">
<xsl:variable name="result-text">
<xsl:text/>0<xsl:apply-templates select="/*/RECEIPT[1]"
mode="equation"/>
</xsl:variable>
<xsl:variable name="result" select="number(\$result-text)"/>

<xsl:value-of select="\$result"/>
</xsl:template>

<xsl:template match="RECEIPT" mode="equation">
<xsl:param name="result" select="0"/>
<xsl:variable name="this" select="\$result + ( qtyRcpt * line/pr )"/>
<xsl:choose>
<xsl:when test="following-sibling::RECEIPT">
<xsl:apply-templates select="following-sibling::RECEIPT[1]"
mode="equation">
<xsl:with-param name="result" select="\$this"/>
</xsl:apply-templates>
</xsl:when>
<xsl:otherwise>
<xsl:value-of select="\$this"/>
</xsl:otherwise>
</xsl:choose>
</xsl:template>

</xsl:stylesheet>

SECOND EXAMPLE:

<xsl:stylesheet
xmlns:xsl="http://www.w3.org/1999/XSL/Transform";
version="1.0">

<xsl:template name="total-sales-value">
<xsl:param name="list"/>
<xsl:choose>
<xsl:when test="\$list">
<xsl:variable name="first" select="\$list[1]"/>
<xsl:variable name="total-of-rest">
<xsl:call-template name="total-sales-value">
<xsl:with-param name="list" select="\$list[position()!=1]"/>
</xsl:call-template>
</xsl:variable>
<xsl:value-of select="\$first/sales * \$first/price +
\$total-of-rest"/>
</xsl:when>
<xsl:otherwise>0</xsl:otherwise>
</xsl:choose>
</xsl:template>

<xsl:template match="/">
<xsl:variable name="total">
<xsl:call-template name="total-sales-value">
<xsl:with-param name="list" select="//book"/>
</xsl:call-template>
</xsl:variable>
Total sales value is: <xsl:value-of select="format-number(\$total,
'\$#.00')"/>
</xsl:template>
</xsl:stylesheet>

QUESTION:

In Mr. Kay's example, why does the variable \$total-of-rest indeed contain
the total
and not just the result of the addition in the last recursion?

--------------------------------------------------------------------
mail2web - Check your email from the web at
http://mail2web.com/ .

--~------------------------------------------------------------------
XSL-List info and archive:  http://www.mulberrytech.com/xsl/xsl-list
To unsubscribe, go to: http://lists.mulberrytech.com/xsl-list/
or e-mail: <mailto:xsl-list-unsubscribe(_at_)lists(_dot_)mulberrytech(_dot_)com>
--~--

```
```
--~------------------------------------------------------------------
XSL-List info and archive:  http://www.mulberrytech.com/xsl/xsl-list
To unsubscribe, go to: http://lists.mulberrytech.com/xsl-list/
or e-mail: <mailto:xsl-list-unsubscribe(_at_)lists(_dot_)mulberrytech(_dot_)com>
--~--

```
 Current Thread [xsl] Two versions of sum over node list by recursion--why and how does second one work?, hanged(_dot_)man(_at_)lycos(_dot_)com Re: [xsl] Two versions of sum over node list by recursion--why and how does second one work?, David Carlisle Re: [xsl] Two versions of sum over node list by recursion--why and how does second one work?, andrew welch RE: [xsl] Two versions of sum over node list by recursion--why and how does second one work?, Michael Kay Re: [xsl] Two versions of sum over node list by recursion--why and how does second one work?, Dimitre Novatchev <=